2014
DOI: 10.3389/fncel.2014.00133
|View full text |Cite
|
Sign up to set email alerts
|

Fast detection of extrasynaptic GABA with a whole-cell sniffer

Abstract: Gamma-amino-butyric acid (GABA) is the main inhibitory transmitter of the brain. It operates by binding to specific receptors located both inside and outside synapses. The extrasynaptic receptors are activated by spillover from GABAergic synapses and by ambient GABA in the extracellular space. Ambient GABA is essential for adjusting the excitability of neurons. However, due to the lack of suitable methods, little is known about its dynamics. Here we describe a new technique that allows detection of GABA transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Because of the activity dependency, measuring ambient GABA is challenging, and the diversity of experimental conditions and analytical methods makes comparisons of tonic inhibition between studies quite difficult (Bright & Smart, ; Christensen et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because of the activity dependency, measuring ambient GABA is challenging, and the diversity of experimental conditions and analytical methods makes comparisons of tonic inhibition between studies quite difficult (Bright & Smart, ; Christensen et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…The assumption is consistent with previous reports demonstrating a dependency of ambient GABA levels on neuronal activity (Lerma et al 1986;Rowley et al 1995;Kennedy et al 2002;de Groote & Linthorst, 2007;Vanini et al 2011). Because of the activity dependency, measuring ambient GABA is challenging, and the diversity of experimental conditions and analytical methods makes comparisons of tonic inhibition between studies quite difficult (Bright & Smart, 2013;Christensen et al 2014).…”
Section: Effects Of Extrasynaptic Gabamentioning
confidence: 99%
“…A GABA sensor that allows time-resolved micromolar spatial resolution in living tissue would be a great benefit to explore how GABA compartmentation is regulated. Some progress has occurred using whole-cell patch clamp with human embryonic kidney cells expressing GABA receptors [61] or GABA imprinted electrodes [62].…”
Section: Topology and The Regulation Of Local Gaba Concentration Thementioning
confidence: 99%
“…By varying the concentration of GABA in the puff pipette, we found that the responses increased monotonically with GABA and saturated at concentrations above 1 m m (Christensen et al . ). These results demonstrate that our sensor can be used to detect GABA transients.…”
Section: Resultsmentioning
confidence: 97%
“…HEK cells recorded in voltage-clamp mode transduced extracellular GABA into an electrical current (Christensen et al 2014). When held at 0 mV, the GABA sniffer responded to brief GABA puff (1 mM) by strong transient outward currents that were blocked by gabazine (10 μM) and picrotoxin (50 μM) ( Fig.…”
Section: Resultsmentioning
confidence: 99%